The first fossil representative of the water strider subfamily Ptilomerinae (Heteroptera: Gerromorpha: Gerridae) in the Oligocene paleolake of Murs (southern France) with some palaeoecological considerations - Nel, André; Mennecart, Bastien; Spasojevic, Tamara; Viertler, Alexandra; Maridet, Olivier; Costeur, Loïc; Garrouste, Romain; Coster, Pauline (European Journal of Taxonomy, 2023)
Oligoptilomera luberonensis gen. et sp. nov., first fossil representative of the gerrid subfamily Ptilomerinae, is described and figured from the Oligocene of Murs (Vaucluse, Southern France). Extant Ptilomerinae live in streams in warm climates, of the Indo-Malaysian, eastern Palaearctic, and Papouan regions. The discovery of this Oligocene French Ptilomerinae is in accordance with the putative age of the subfamily, at least older than the Eocene, and with the Indo-Malaysian affinities previously recorded for some other insects from the Oligocene of France. The two insect assemblages of Murs and Céreste are compared and the differences discussed. Although of similar ages, that from Murs was possibly corresponding to a more shallow water paleolake than that of Céreste.